Long-term survival in a male patient with Müllerian adenocarcinoma of the pelvis: a 15-year case report - Ranieri, Girolamo; Porcelli, Mariangela; Mastrorosa, Alessandro; Di Palo, Alessandra; Ferrari, Cristina; Zito, Alfredo Francesco; Ammendola, Michele; Laface, Carmelo; Mastrandrea, Giovanni; Berardone, Simona (Frontiers in Oncology, 2025)
BackgroundMüllerian adenocarcinoma is a very rare and aggressive cancer originating from the uterus and ovary, affecting almost exclusively women. Few cases of extragenital Müllerian adenocarcinomas have been reported, in various locations ranging from pelvic peritoneum to diaphragm peritoneum. Very few cases of Müllerian adenocarcinoma in men have been reported in scientific literature, usually localized in the prostate seminal vesicles and testicles, associated to a very poor prognosis.Case summaryIn this paper, we describe the unique clinical case of a man affected by advanced Müllerian adenocarcinoma on the left side of the pelvis, treated with a combination of surgery, chemotherapy, and radiotherapy, with a long follow-up. Patient survival was exceptional (almost 15 years from diagnosis), and the patient experienced a good quality of life during the numerous treatments. To the best of our knowledge, this is the first case report regarding a Müllerian adenocarcinoma of the pelvis in a man treated with a multimodal therapy approach and with a very long follow-up and very long survival. In consideration of the embryological origin of ovaries from Müllerian ducts and the absence of specific guidelines for standard treatment for this tumor, the patient was treated as if he had ovarian cancer, with optimal results.ConclusionsThe management of this patient with modern available lines of chemotherapy classically employed in ovarian cancer plus radiotherapy combined with several bouts of cytoreductive surgery could explain this long survival.